To match the given polynomials on the left with their factors on the right, let's factor the polynomials on the left and see which pairs match up with the factors provided.
- Polynomial: \( 8x^3 + 1 \)
This can be factored using the sum of cubes formula:
\[ a^3 + b^3 = (a + b)(a^2 - ab + b^2) \]
Here, \( a = 2x \) and \( b = 1 \):
\[ 8x^3 + 1 = (2x + 1)(4x^2 - 2x + 1) \]
Match: \( 8x^3 + 1 \) with \( 2x + 1 \) and \( 4x^2 - 2x + 1 \)
- Polynomial: \( 8x^3 - 1 \)
This can be factored using the difference of cubes formula:
\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \]
Here, \( a = 2x \) and \( b = 1 \):
\[ 8x^3 - 1 = (2x - 1)(4x^2 + 2x + 1) \]
Match: \( 8x^3 - 1 \) with \( 2x - 1 \) and \( 4x^2 + 2x + 1 \)
Summary of Matches:
- \( 8x^3 + 1 \) matches with \( 2x + 1 \) and \( 4x^2 - 2x + 1 \).
- \( 8x^3 - 1 \) matches with \( 2x - 1 \) and \( 4x^2 + 2x + 1 \).
List of Matches:
- \( 8x^3 + 1 \) → \( 2x + 1 \), \( 4x^2 - 2x + 1 \)
- \( 8x^3 - 1 \) → \( 2x - 1 \), \( 4x^2 + 2x + 1 \)
The other polynomials \( 4x^2 + 4x + 1 \) and \( 4x^2 - 4x - 1 \) do not correspond to any cubic polynomials mentioned above for factoring.